Indigenous peoples’ rights in Bolivia : Philosophy, law and politics in a pluri-national state - CAMMARATA, ROBERTO (Edizioni Altravista, 2016)
In recent decades, indigenous groups in Bolivia have gained strength, reclaiming their identity as Indigenous Peoples and First Nations, and increasing their levels of organization and participation in the democratic process. The new Bolivian Constitution has been seen by many experts as one of the most comprehensive constitutions for indigenous rights and autonomy in the world, but the political scenario in Bolivia is highly complex, as certain sectors are resistant to the effective implementation of these rights. According to many critical voices, notwithstanding the legal changes, these rights very often fail to be respected and enforced in practice. This brief intervention offers a snapshot of the recognition of indigenous rights in Bolivia and the challenge they have to face, in particular as far as land rights are concerned.